THE AL 'AFWU (FORGIVING EACH OTHER) APPROACH IN RESTORATIVE JUSTICE FOR DISPUTING MUSLIMS - Nugroho, Taufiq; Samudera, Kiki; Cakraningrat, Karisma; Maulana, Jasmine Fahira; Ratnasari, Yenny; Budiono, Arief (Universitas Muhammadiyah Tangerang, 2024)
In criminal law, restorative justice is a new thing. Previously, Islam had already known the term restorative justice in its criminal law (jinayah) with the term al-istiadah. Forms of application of al-istiadah include islah (peace) and al-'afwu (forgiveness). As something new, the implementation of restorative justice has resulted in reforms in the criminal justice system in Indonesia. In this study, the author tries to explain the benchmarks for implementing restorative justice in terms of the values of the mutual forgiveness approach (al 'afwu) for those who believe in Islam. This descriptive research uses normative legal research methods that prioritize secondary data and are analytical and descriptive in nature. The results of this study indicate a benchmark for the implementation of restorative justice as an alternative settlement of criminal cases using the Al 'Afwu approach in the context of resolving criminal cases for Muslims. The restorative justice system strives to fix or recover the impacts of a criminal act. But there needs to be the perpetrators’ efforts to return or fix the condition due to the impacts caused by the criminal actions they carried out.